First-principles study of beryllium thermodynamics and clustering mechanism in molybdenum: Effects of vacancies and self-interstitial atoms - Aoyu Mo; Haijun Li; Fuquan Guo; Xiaowei Ma; Yunshan Xiong; Peng Shao; Bo Li; Kun Jie Yang; Yue-Lin Liu; Quan-Fu Han (Nuclear Materials and Energy)
The clustering behavior of beryllium (Be) following plasma irradiation is of particular significance for molybdenum (Mo) in future fusion devices. Using first-principles calculations combined with thermodynamic models, the optimal configuration for Be clustering in Mo has been clearly determined, with a particular focus on the effects of vacancies and self-interstitials (SIAs). As the initial form of nucleation, the physical origin of Be-Be pair binding energy in Mo has been shown to be primarily dominated by the charge density at their location. Based on all of our computational results, a potential clustering mechanism for the formation of Be-rich regions in Mo is proposed: Be atoms first aggregate at interstitial sites, forming Ben clusters. When the number of Be atoms reaches six, they form an approximately “octahedral” structure, displacing a central Mo atom and generating a Be6V cluster and an SIA. They act as nucleation sites that continue to attract more Be atoms, growing into larger BenV and Ben-SIA clusters. As the Ben-SIA clusters expand, excess Be atoms displace more Mo atoms, creating additional SIAs and vacancies and further propagating the formation of Ben-SIA and BenV clusters. This cascading process ultimately results in the development of Be-rich regions within Mo. Our results provide significant data support for advancing Mo as a primary mirror material and also offer valuable theoretical insights into the aggregation behavior of impurities in metals under irradiation conditions.